Media Exposure, Environmental Performance, Company Size And Its Influence On Carbon Emission Disclosure - Aruning Puspita, Dyah; Christa Delvia; Djoko Sugiono (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to determine the influence of media exposure, environmental performance, and company size on mining companies listed on the Indonesia Stock Exchange. This study has the quantitative nature of causality. The population contained in this study is companies in the mining sector listed on the Indonesia Stock Exchange which were then obtained as many as 36 companies. The technique used in the sampling process in this study was purposive sampling which in the end obtained 12 companies that had met the criteria. The method that researchers use is to use the PLS method to test the influence of research variables using SmartPLS 4 software. This result shows that media exposure has a significant effect on carbon emission disclosure, environmental performance has a significant effect on carbon emission disclosure, and company size has a significant effect on carbon emission disclosure.